Pengaruh Effective Tax Rate, Bonus Scheme, Tunneling Incentive, dan Leverage terhadap Transfer Pricing dengan Size sebagai Variabel Moderasi : (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2018-2021) - Luthfi Yudhistira; Inge Lengga Sari Munthe; Rizki Yuli Sari (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2023)
Transfer pricing is a transaction price that is included in every product or service from one company to another or from one industry to another with the same or different companies and has a special relationship. This study aims to determine the effect of effective tax rates, bonus schemes, tunneling incentives, and leverage on transfer pricing with size as a moderating variable in manufacturing companies listed on the IDX for the 2018-2021 period. The analytical method used is logistic regression analysis and Moderated Regression Analysis (MRA). The results of the study show that the bonus scheme, tunneling incentive, leverage, and size have a partial effect on transfer pricing. Meanwhile, the effective tax rate has no partial effect on transfer pricing. Size is able to moderate the effect of bonus schemes, tunneling incentives, and leverage on transfer pricing. However, size is unable to moderate the effect of the effective tax rate on transfer pricing.